A tale for the time being [compact disc, unabridged] - Ozeki, Ruth. 1956- (Blackstone Audio, 2013)
In Tokyo, sixteen-year-old Nao has decided there's only one escape from her aching loneliness and her classmates' bullying. But before she ends it all, Nao first plans to document the life of her great grandmother, a Buddhist nun who's lived more than a century. A diary is Nao's only solace--and will touch lives in ways she can scarcely imagine. Across the Pacific, we meet Ruth, a novelist living on a remote island who discovers a collection of artifacts washed ashore in a Hello Kitty lunchbox--possibly debris from the devastating 2011 tsunami. As the mystery of its contents unfolds, Ruth is pulled into the past, into Nao's drama and her unknown fate, and forward into her own future.